SINTESIS MULLITE MELALUI RUTE PROSES GEL - Walmiki Samadhi, Tjokorde
Abstract : Mullite (3A12O3.2SiO2) is one of the ceramic materials having a bright production prospects as advanced ceramics intermediate material in Indonesia. Among the various mullite synthesis routes, the gel process route has several advantages. It is relatively simple, yet capable of producing mullite product with good characteristics. Current studies on gel processes mainly utilized relatively expensive metalorganic precursors, though it is already recognized that inorganic precursors can also be used as reactants in gel processes. A research aimed at studying the viability of alternative gel process route utilizing inorganic precursors had been undertaken. Precursors used in this research were aluminum nitrate solution and silicic acid sol. The core of this research is a series of batch syntheses experiment of pre-mullite gel. Process viability was evaluated from the thermal behaviour and phase development of gel product. Process variables studied are initial pH of reacting mixture and method of coprecipitation. The range of initial pH value is 1.5 - 3.0. The molar ratio between alumina and silica corresponded to that of stoichiometric mullite. For the process route investigated, it was found that coprecipitation via dropwise addition of precipitating agent into the reactant mixture with an initial pH of 1.5 - 2.0 produced the most reactive pre-mullite gels (gels which directly form mullite on firing). Other values of variables, which included operation at initial pH higher than 2.0 and / or coprecipitation by adding reactant mixture into solution of precipitating agent, produced less reactive gels which formed only spinel or spinel-mullite mixture on firing.